THE MODERATION EFFECT OF BOARD DIVERSITY: ESG DISCLOSURE AND FINANCIAL PERFORMANCE IN INDONESIAN - Wiguna, Meilda; Silviani, Amanda Agnes; Hardi, Hardi; Hariyani, Eka; Supriono, Supriono; Natariasari, Riska (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2025)
This study examines the influence of Environmental, Social, and Governance (ESG) on financial performance in Indonesian non-financial companies, with board diversity as a moderating variable. ESG has emerged as a critical factor affecting investor perception and business operations amid growing environmental and social concerns. However, its effectiveness depends on company structure, particularly employee alignment. Using quantitative methods, the study analyzes non-banking firms listed on the Indonesian Stock Exchange through multiple and moderated regressions. Results show ESG positively impacts financial performance, further amplified by board diversity in gender, age, and professional background. This underscores the role of diverse leadership in maximizing ESG benefits. Companies are encouraged to enhance diversity to improve ESG effectiveness, driving stronger financial outcomes and advancing sustainable business practices.